Discrete Breathers in One- and Two-Dimensional Lattices - Butt, Imran Ashiq (2006)
Discrete breathers are time-periodic and spatially localised exact solutions in translationally invariant nonlinear lattices. They are generic solutions, since only moderate conditions are required for their existence. Closed analytic forms for breather solutions are generally not known. We use asymptotic methods to determine both the properties and the approximate form of discrete breather solutions in various lattices.